Eradication of minimal residual disease improves overall and progression‐free survival in patients with chronic lymphocytic leukaemia, evidence from NCRN CLL207: a phase II trial assessing alemtuzumab consolidation. (29th December 2016) - Varghese, Abraham M.; Howard, Dena R.; Pocock, Christopher; Rawstron, Andy C.; Follows, George; McCarthy, Helen; Dearden, Claire; Fegan, Christopher; Milligan, Donald; Smith, Alexandra F.; Gregory, Walter; Hillmen, Peter; et al.
Summary: With immunochemotherapy, remission duration and survival in patients with chronic lymphocytic leukaemia is dependent on the level of minimal residual disease (MRD) after treatment. This phase II trial assessed alemtuzumab consolidation post‐chemotherapy in patients who responded with persistent low levels of detectable disease. Blood was screened for MRD using multi‐parameter flow cytometry, 6–24 months post‐chemotherapy. MRD‐positive participants received alemtuzumab 30 mg subcutaneously 3 times weekly for 6 weeks. Following a marrow assessment, MRD‐negative participants or non‐responders stopped therapy and MRD‐positive participants with 1 + log reduction had 6 more weeks of alemtuzumab. Alemtuzumab consolidation was received by 47 participants. One death and 19 of 22 serious adverse events reported from 17 (36%) participants were alemtuzumab‐related. MRD eradication from blood and bone marrow was achieved in 39 (83%) participants at the end of consolidation, with 18 (38%) remaining MRD‐negative in the blood 6 months later. Of the 18 participants who were MRD‐negative at 6 months, the median time to MRD relapse was 46 months, which was similar to patients who were MRD‐negative at baseline and were followed up. The 5‐year progression‐free survival (PFS) and overall survival (OS) of participants who were MRD‐negative at 6 months was significantly better than MRD‐positive participants [PFS: 78% vs. 39% ( P = 0·010), OS: 89% vs. 64% ( P = 0·029)].